QUANTITATIVE ANALYSIS OF HYPERAUTOFLUORESCENT RINGS TO CHARACTERIZE THE NATURAL HISTORY AND PROGRESSION IN RPGR-ASSOCIATED RETINOPATHY. Issue 12 (December 2018) - Tee, James J. L.; Kalitzeos, Angelos; Webster, Andrew R.; Peto, Tunde; Michaelides, Michel
Abstract : Purpose: Quantitative analysis of hyperautofluorescent rings and progression in subjects with retinitis pigmentosa associated with retinitis pigmentosa GTPase regulator ( RPGR ) gene mutations. Methods: Prospective observational study of 46 subjects. Ring area, horizontal and vertical diameter measurements taken from outer and inner ring borders. Intraobserver repeatability, baseline measurements, progression rates, interocular symmetry, and association with age and genotype were investigated. Results: Baseline ring area was 11.8 ± 13.4 mm 2 and 11.4 ± 13.2 mm 2 for right and left eyes, respectively, with very strong interocular correlation (r = 0.9398; P < 0.0001). Ring area constriction was 1.5 ± 2.0 mm 2 /year and 1.3 ± 1.9 mm 2 /year for right and left eyes, respectively, with very strong interocular correlation (r = 0.878, P < 0.0001). Baseline ring area and constriction rate correlated negatively with age (r = −0.767; P < 0.0001 and r = −0.644, P < 0.0001, respectively). Constriction rate correlated strongly with baseline area (r = 0.850, P < 0.0001). Age, but not genotype, exerted a significant effect on constriction rates ( P < 0.0001), with greatest rates of progression seen in younger subjects. An exponential decline overall was found. Conclusion: This study provides disease-specific baseline values and progression rates together with a repeatability assessment of fundus autofluorescence metrics. Our findings can guide future treatment trials and contribute to the clinical care of patients with RPGR -associated retinitis pigmentosa. Abstract : Seventy to eighty percent of X-linked retinitis pigmentosa are associated with RPGR mutations. This disease-specific autofluorescence study provides data on baseline values, progression rates, symmetry, and associations with age and genotype. These findings can guide future treatment trials and contribute to clinical care of patients with RPGR -associated retinitis pigmentosa.